Mix Indonesian Code in Buying and Selling at Simpang Limun Market in Medan Sociolinguistic Study - Rahmi, Sri (Institute of Computer Science (IOCS), 2019)
This thesis describes: Mix code in Indonesian for the Buy and Sell situation at Simpang Limun Market, Medan. The problem studied is how to mix code in the market and determine the type of words in the code mix. In this research, the method used is the observation method. The technique used is the basic technique of tapping with advanced techniques of observation and recording techniques. The data assessment method is an equivalent method followed by the basic technique of sorting the determinants. The theory used in this study uses the sociolinguistic theory approach, bilingualism, mix codes and types of words. Furthermore, the results of this study on code mixing that occurred in Pasar Simpang Limun Medan were found words and phrases. And in the event of code mixing, there was an inner code-mixing in the form of a regional language that inserted in the first language, namely Indonesian, and outher code-mixing in the form of a foreign language, namely English which inserted into the first language, namely the language. Indonesia. The types of words according to Keraf are divided into four parts, namely: 15 nouns, 5 verbs, 9 adjectives, and 2 tasks, and what often appears is the type of noun ( noun).